From Scrolls to Traditions : A Festschrift Honoring Lawrence H. Schiffman - Miller, Stuart S.,; Swartz, Michael D.,; Fine, Steven,; Grunhaus, Naomi,; Jassen, Alex P., (The Brill Reference Library of Judaism ;, 2021)
This Festschrift in honor of Professor Lawrence H. Schiffman, a renowned authority on the Dead Sea Scrolls and Rabbinic Judaism, includes contributions by twenty of his former doctoral students, now colleagues. The volume is divided into two sections, the "Biblical and Second Temple Period" and "Rabbis, Other Jews, and Neighboring Cultures." The diverse topics covered and the wide range of interdisciplinary approaches employed reflect Professor Schiffman's success in cultivating a school of scholars who are making unique contributions to the study of the Jews and Judaism.